Mainstreaming FATA: A Public Policy Imperative - Khan, Muhammad Zaheer (Journal of History Culture and Art Research, 2018)
The paper aims to analyze the situation of Federally Administered Tribal Areas (FATA) in the context of Frontier Crimes Regulation (FCR). It analyzes how a suitable public policy mechanism needs to be devised and implemented by replacing the old and an irrational FCR in FATA. It extensively examines the theoretical and conceptual perspectives on the public policy, the policy formation and policy factors. The Parsons’ seven steps model of policy framework has been theorized on the study for developing the appropriate policy. The qualitative methodology has been used to get in-detail and in-depth information about the governance mechanism and prevailing issues of FATA. There are three main elements; first getting familiar with the problem, second relevant players and third devising a policy. The study proposes that new public policy for FATA must be carried out with the consultation of the official (legislative, judiciary and executive) and unofficial stakeholders (civil society, media, ethnic groups, public opinion etc).